Pembentukan Kelompok Belajar untuk Siswa pada Pembelajaran Daring - Dewi Sri Utami; Oce Datu Appulembang (Sukma: Jurnal Pendidikan, 2022)
The Covid-19 pandemic has brought changes in human life. The learning process that was originally carried out directly in the classroom, now has to be done at home by utilizing technology and internet networks. Online learning makes communication between students and their friends limited and students’ ability to work together is reduced. For this reason, as a teacher, you must be able to design learning methods that can make students still able to have good communication with their friends. The method of forming study groups for students is one of the effective methods used in the midst of online learning as it is today. Therefore, the purpose of writing this paper is to explain the importance of group formation methods in developing student collaboration from a Christian perspective. This paper was prepared using a descriptive qualitative research method. Christian teachers when dividing students into groups, must divide fairly and see students as valuable creations in the likeness and image of God. So that in the learning process in groups, Christian teachers must be able to guide students not only to learn about love but to be able to practice love itself in their groups. The existence of a group formation method is not only useful for developing student collaboration skills, but also allows students to appreciate every difference that exists in their group.